Kinerja Anggota Dewan Perwakilan Rakyat Daerah Kabupaten Majalengka Berbasis Kecerdasan - Masduki Masduki (Journal of Innovation in Management, Accounting and Business, 2022)
This study has the following objectives: First, to determine the level of intelligence (intellectual, emotional, and spiritual), as well as the performance of members of the DPRD Majalengka Regency; second, to find out how much influence intelligence has on the performance of DPRD members in Majalengka Regency. The research method used is a survey of 50 members of the DPRD Majalengka Regency. Data analysis was carried out in three stages: First, the research instrument test, data transformation, and data normality test; second, correlation analysis and coefficient of determination analysis; and third, hypothesis testing. The results showed that the level of intelligence (intellectual, emotional, and spiritual) of the DPRD members of Majalengka Regency in the majority was in the high category, as well as the level of performance was included in the high category. The results of hypothesis testing indicate that intelligence (intellectual, emotional, and spiritual) has a significant effect on the performance of DPRD members of Majalengka Regency, either partially or simultaneously.